Peran Sekolah dalam Membentuk Karakter Sopan Santun Siswa SD Adinda Surabaya - Ayu Umi Salamah; Muhammad Thamrin Hidayat; Muslimin Ibrahim; Akhwani Akhwani (Journal on Education, 2023)
Character education is an effort to form the habit of doing good, so that in carrying out character education, polite character values are also needed. This study aims to determine the constraints and barriers to the school's role in shaping the polite character of SD Adinda Surabaya students. This study uses a descriptive qualitative research method that aims to define and explain how the role of the school in shaping the character of student manners. Data collection techniques using observation, interviews, and questionnaires. From the results of the data obtained then analyzed, that the school's role in shaping the polite character of SD Adinda Surabaya students, the school as a facilitator by providing character values and understanding to students through habituation activities programs for students, as well as being a role model in polite character . There are supporting and inhibiting factors in shaping the polite character of students including: support for the participation of school members including principals, teachers, employees and students, lack of support from parents and family, daily student friendship groups that are not conducive